2017
DOI: 10.1002/jcph.996
|View full text |Cite
|
Sign up to set email alerts
|

Potential Drug–Drug Interactions Among Critically Ill Pediatric Patients in a Tertiary Pulmonary Center

Abstract: Patients in the pediatric intensive care unit (PICU) are at increased risk of potential drug-drug interactions (pDDIs) because of the complexity of pharmacotherapy. The current study aimed to assess the rate, pattern, risk factors, and management of pDDIs in the PICU of an academic pulmonary hospital. A prospective observational study was conducted for 6 months. Pharmacotherapy data of PICU-admitted patients were evaluated by a clinical pharmacologist. Interacting drugs, reliability, mechanism, potential outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…This sequence is comparable to most of the drug interaction studies that have been done in this population. [3,10,21,23] Dai et al [2] reported that 70% of the interactions in their study were either major or contraindicated. We did not find any interaction that is "contraindicated," as opposed to the studies of Hassanzad et al [23] and Dai et al [2] which had 0.5% and 0.8% contraindicated PDDIs, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence is comparable to most of the drug interaction studies that have been done in this population. [3,10,21,23] Dai et al [2] reported that 70% of the interactions in their study were either major or contraindicated. We did not find any interaction that is "contraindicated," as opposed to the studies of Hassanzad et al [23] and Dai et al [2] which had 0.5% and 0.8% contraindicated PDDIs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[3,10,21,23] Dai et al [2] reported that 70% of the interactions in their study were either major or contraindicated. We did not find any interaction that is "contraindicated," as opposed to the studies of Hassanzad et al [23] and Dai et al [2] which had 0.5% and 0.8% contraindicated PDDIs, respectively. The high level of PDDI prevalence in our study could be due to several factors such as the underlying medical condition, the presence of extensive polypharmacy, and long duration of hospital stay, to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was reported that the ratio of 'contraindicated' DDI was 0.2%, 'serious' DDIs were 7.5%, and 'significant-monitor closely' were 62.8% (7). The large difference in the prevalence of clinically important potential drug interactions might be due to the critical medical conditions of pediatric inpatients, which make them more susceptible to the administration of multiple drugs, complex treatment regimens, and care by physicians of different specialties for consultations (15,16). In addition, hospitalized pediatric patients are vulnerable to medication-related issues because of off-label prescribing of drugs, lack of therapeutic profiles for rare drugs, and weight-based dosing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…As with any screening tool, effectiveness of DDI checkers is much higher if used in subpopulations with high risk of the target problem. Risk factors for DDIs in patients at ICU were studied in several settings, and the following were repeatedly reported: the length of stay and number of drugs or therapeutic groups prescribed (3)(4)(5)(6). However, a few other risk factors may be of importance, especially prescription of certain drug groups which are prone to DDIs, like anticonvulsants or anticoagulans (3), but their true significance remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%